Carboxymethyl Hyaluronan-Stabilized Nanoparticles for Anticancer Drug Delivery. (10th September 2015) - Woodman, Jessica L.; Suh, Min Sung; Zhang, Jianxing; Kondaveeti, Yuvabharath; Burgess, Diane J.; White, Bruce A.; Prestwich, Glenn D.; Kuhn, Liisa T.
Abstract : Carboxymethyl hyaluronic acid (CMHA) is a semisynthetic derivative of HA that is recognized by HA binding proteins but contains an additional carboxylic acid on some of the 6-hydroxyl groups of the N-acetyl glucosamine sugar units. These studies tested the ability of CMHA to stabilize the formation of calcium phosphate nanoparticles and evaluated their potential to target therapy resistant, CD44 + /CD24 −/low human breast cancer cells (BT-474EMT ). CMHA stabilized particles (nCaP CMHA ) were loaded with the chemotherapy drug cis -diamminedichloroplatinum(II) (CDDP) to form nCaP CMHA CDDP. nCaP CMHA CDDP was determined to be poorly crystalline hydroxyapatite, 200 nm in diameter with a −43 mV zeta potential. nCaP CMHA CDDP exhibited a two-day burst release of CDDP that tapered resulting in 86% release by 7 days. Surface plasmon resonance showed that nCaP CMHA CDDP binds to CD44, but less effectively than CMHA or hyaluronan. nCaP CMHA-AF488 was taken up by CD44 + /CD24 − BT-474EMT breast cancer cells within 18 hours. nCaP CMHA CDDP was as cytotoxic as free CDDP against the BT-474EMT cells. Subcutaneous BT-474EMT tumors were more reproducibly inhibited by a near tumor dose of 2.8 mg/kg CDDP than a 7 mg/kg dose nCaP CMHA CDDP. This was likely due to a lack of distribution of nCaP CMHA CDDP throughout the dense tumor tissue that limited drug diffusion.